STRUKTUR KOMUNITAS MANGROVE DI PESISIR DESA TATENGESAN, KECAMATAN POSOMAEN, KABUPATEN MINAHASA TENGGARA - Maykel R Munaimbala; Carolus P Paruntu; Antonius P Rumengan (Sam Ratulangi University, 2021)
The purpose of this study was to examine the structure of the mangrove community on the coast of Tatengesan, Posomaen District, Southeast Minahasa Regency, North Sulawesi. The data collection of the mangrove community structure used the line transect quadratic method measuring 10 m x 10 m 5 times. The research implementation period is 6 (six) months in 2021, starting from the preparation of proposals, data analysis, examination of research results, and the implementation of thesis examinations. Based on the results of the study, found 3 types of mangroves, namely: Rhizophora apiculata, Rhizophora mucronata, and Bruguiera gymnorrhiza. The value of the highest species relative density was found on transect 2 with a value of 88.33% by R. mucronata. For the value of the highest relative frequency of species on transects 1,2 and 3 by R. mucronata, namely 8.3 cm/m. The highest relative species cover was R. mucronata with a value of 76.99% on transect 2. The highest important value index was found in R. mucronata, which was 220.88 on transect 2. The highest diversity index was found on transect 3 with a value of 0.85. The highest evenness index was found on transect 1 with a value of 0.99. For further research, it is necessary to conduct an inventory of mangrove species using the roaming method to find out all the species in the research location.Keywords: Mangrove, Tatengesan, Community, Diversity and Evenness